Pemanfaatan Media Edukatif Game Clash of Champions dalam Meningkatkan Minat Belajar Pembelajaran Matematika Sekolah Dasar - Risa Taviya Putri; Slamet Slamet; Fals Aldino (CV. Lentera Literasi Indonesia, 2026)
This study aims to assess the effectiveness of Ruangguru's Clash of Champions (COC) game as an interactive learning tool, focusing on